PENAFSIRAN AKAL DALAM AL-QUR’AN - Hodri, Hodri (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2013)
It?s inevitable that the Koran will always be a reference (marja?) for Muslims in every thought and action, followed later by al-Sunnah in the second position, both as a reference in understanding the Koran or as independent sources in understanding and resolve specific cases. This fact has prompted the birth of various patterns of interpretation or comments of the scholars of Koran which continues to experience dynamic methodoligical growth, from tahlîlî, bi al-ma?thûr, adabî wa ijtimâ?î, sûfî, to the mawdû?î or thematic model. This article will discuss the intellect (al-?aql) within teh Koran perspective, namely effort to understand a thematic topic. Intellect (al-?aql) is one of debate topic among Muslims, especially among theologians or mutakallimîn against philosophers, who have not obtained a satisfactory intersection. This paper see